DEVELOPMENT OF FLIP CHART LEARNING MEDIA IN VIRUS MATERIALS FOR GRADE X HIGH SCHOOL STUDENTS - Aan Rinda Erviana; Devita Sulistiana; Maratus Sholihah (JOSAR (Journal of Students Academic Research), 2018)
Based on preliminary observations that show that as many as 51,2% of 123 students stated that biology lessons were a difficult lesson. As many as 77,3% of students experience learning difficulties on virus material. Learning activities can not be separated from the use of learning media. This development aims to know the valid of flip chart learning media on virus material for high school students of class X. This research is a Research & Development (R&D) study using the Thiagarajan et all 4D development model, which is limited to the develop stage. This development research resulted in flip chart learning media through validation by a team of experts getting a total value of 80% with a valid category. Readability test results by students amounted to 94% with a very valid category. Flip chart learning media is worthy of being used as a learning medium on virus material.